A field survey of eight common potato pathogens in China based on integrated-loop-mediated isothermal amplification assays - Zhang, X.; Chen, H.; Wu, J.; Wang, X.; Wang, S.; Chen, J.; Yu, Q.; Zhang, Z.; Zheng, X.; Zeng, J.; Dong, S. (2024)
Various pathogens from oomycete, fungi, and bacteria kingdoms can infect potato and significantly reduce potato yield. The early diagnosis of potato pathogens is important for tracing disease epidemics and the subsequent disease management. Loop-mediated isothermal amplification (LAMP) is a critical technique for pathogen detection, but available LAMP assays do not effectively meet the requirement of field diagnoses due to complexities including co-infection of different pathogens. Hence, this study aims to develop integrated-LAMP assays (iLAMPs) for simultaneous detection of eight common potato pathogens and apply iLAMPs to pathogen detection in field samples from the four main potato-growing regions of China in 2023. Therefore, eight sets of primers showing gene- and genus-specificity were designed and used for iLAMPs to determine their specificity, sensitivity, and visualization. Subsequently, iLAMPs-mediated pathogen detection revealed that 72.82% of 206 diseased leaves and 84.94% of 239 diseased tubers carry more than one pathogen. The detection rate for each pathogen significantly varies from 1.94 to 65.53% in diseased leaves, and ranges from 26.78 to 52.72% in diseased tubers, respectively. In addition, the detection rate of Phytophthora infestans and Alternaria solani positively correlates in both leaves and tubers, especially for those samples from the southwestern and southern regions. Taken together, iLAMPs developed in this study enables simultaneous detection of eight common potato pathogens from field samples and may have broad applications in early management of potato diseases.